JENIUS LOKAL DAN TRANSFORMASI BUDAYA: Membaca Ulang Pemikiran Umar Kayam sebagai Refleksi Sejarah untuk Melihat Masa Depan - Kunu, Arifuddin (Journal Communication Spectrum : Capturing New Perspectives in Communication, 2014)
The development of cultural studies today cannot be separated from the various thoughts that fill the cultural discourse space. Culture is demanded to be able to provide solutions to the nation's problems, now it is never devoid of debate. In the midst of the lively debate about culture, reviewing the cultural thinking of local thinkers, becomes important to do, given the strategic role of culture in providing alternative solutions to various daily problems of society [economic, political, social and cultural]. One local thinker whose existence cannot be separated from that cultural discourse is Umar Kayam. Through his ideas on "Cultural Transformation", we are reminded to understand the process of cultural transformation that has been historical in the archipelago and carried out by this nation since centuries ago. The flexibility possessed by our ancestors when "dialoguing" with foreign cultures turned out to be able to produce a culture of synthesis that was so amazing. To cite this article (7th APA style): Kunu, A. (2014). Jenius Lokal dan Transformasi Budaya: Membaca Ulang Pemikiran Umar Kayam sebagai Refleksi Sejarah untuk Melihat Masa Depan [Local Genius and Cultural Transformation]. Journal Communication Spectrum, 4(2), 92-109